2008
DOI: 10.1002/hep.22219
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of computerized tomographic (CT) scanning as a screening modality for esophageal varices

Abstract: Patients with cirrhosis require endoscopic screening for large esophageal varices. The aims of this study were to determine the cost-effectiveness and patient preferences of a strategy employing abdominal computerized tomography (CT) as the initial screening test for identifying large esophageal varices. In a prospective evaluation,102 patients underwent both CT and endoscopic screening for gastroesophageal varices. Two radiologists read each CT independently; standard upper gastrointestinal endoscopy was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 44 publications
(38 reference statements)
1
101
2
3
Order By: Relevance
“…Perri et al suggested that CT was the better initial screening modality compared to endoscopy in terms of cost-effectiveness and patient preferences irrespective of the prevalence of large varices [16]. Liver CT always covers the distal esophagus where all varices occur, and the recent use of multi-detector row CT (MDCT) can provide excellent image quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perri et al suggested that CT was the better initial screening modality compared to endoscopy in terms of cost-effectiveness and patient preferences irrespective of the prevalence of large varices [16]. Liver CT always covers the distal esophagus where all varices occur, and the recent use of multi-detector row CT (MDCT) can provide excellent image quality.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies reported the possibility of evaluation of esophageal varices with CT scans [14][15][16]. Perri et al suggested that CT was the better initial screening modality compared to endoscopy in terms of cost-effectiveness and patient preferences irrespective of the prevalence of large varices [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have investigated the interconnection between findings from both CT and endoscopy, and have demonstrated an agreement between variceal size and radiologic interpretations rather than between variceal size and endoscopic valuation [16,34] . However, CT scanning cannot adequately differentiate between small and large varices nor can it detect red signs on small varices that are also subject to a higher risk of bleeding [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional radiologic examinations such as computed tomography and magnetic resonance have been used to measure liver fibrosis and to identify specific complications of portal hypertension. 4,5 Transient elastography (TE) has demonstrated reliability in noninvasively staging hepatic fibrosis and has been widely accepted for this indication. TE has also been used to assess for the presence of portal hypertension through LS or SS measurements, although performance characteristics have not been sufficient for widespread application.…”
Section: The Shear Effort Of Measurement Of Portal Hypertensionmentioning
confidence: 99%
“…Like chlorcyclizine, phenothiazines also inhibit a late stage of HCV entry, and their anti-HCV activity is unrelated to their antihistamine function. However, unlike chlorcyclizine, phenothiazines inhibit the entry of both HCVpp and HCVcc, 4 suggestive of an antiviral…”
Section: The Shear Effort Of Measurement Of Portal Hypertensionmentioning
confidence: 99%